Seasonal variation and nutrient jointly drive the community structure of macrophytes in lakes with different trophic states - Tian, Yuqing; Lv, Chaochao; Huang, Liangliang; Shan, Hang; Wang, Hao; Wen, Zihao; Yin, Chengjie; Chou, Qingchuan; Zhang, Xiaolin; Ni, Leyi; Cao, Te (Frontiers in Marine Science, 2023)
Introduction Macrophytes are essential for maintaining the health of shallow lake ecosystems, however, the driving and responsive relationship between ecological factors (such as seasonal changes and nutrition, etc.) and plant communities is not yet clear. Methods In this study, we conducted seasonal surveys of macrophyte community composition in lakes with different nutrient states, aiming to understand the incidence relation between macrophyte community diversity, seasonal changes and environmental factors. Results According to the classification criteria of comprehensive nutritional index, there were significant differences in the trophic status of the three lakes. Among them, the Xihu Lake has reached mild eutrophication with a TLI value of 56.33, both Cibi Lake and Haixihai Lake are mesotrophic with TLI value of 36.03 and 33.48, respectively. The results of diversity analysis showed a significant negative correlation between α-diversity (include Species richness, Shannon-Wiener index, Simpson index and Pielou index) and lake nutrient status. Among them, Xihu Lake showed the lowest α-diversity in all seasons, Haixihai Lake exhibited the middle α-diversity, Cibi Lake indicated the highest α-diversity. Non-metric multidimensional ordination showed that there were obvious spatial structures differences among the macrophyte communities in the three lakes. Macrophyte community composition in the three lakes was more similar in summer and autumn, but there was a wider gap in spring and winter. The redundancy analysis indicated distinct differences between diversity index and ecological factors, the eigenvalues of Axis 1 and Axis 2 being, respectively, 36.13% and 8.15%. Environmental factors could explain 44.8% of the total variation in macrophyte communities structure. Among these, nitrogen, phosphorus, water transparency and water temperature contributed 50.2%, 3.5%, 3.8% and 27.5%, respectively. Conclusions In summary, the community structure of macrophytes in plateau shallow lakes is co-regulated by seasons and nutrients.